Improvement of energy recovery from the digestion of waste activated sludge (WAS) through intermediate treatments: The effect of the hydraulic retention time (HRT) of the first-stage digestion. (15th April 2019) - Ruffino, Barbara; Cerutti, Alberto; Campo, Giuseppe; Scibilia, Gerardo; Lorenzi, Eugenio; Zanetti, Mariachiara
Highlights: The effect of digestate age on the performance of intermediate treatments was studied. With a second-stage AD of 20 days, SMP tended to a constant value, irrespective of digestate age. With an overall digestion duration of 20 days, shorter-age digestates were more productive. Energy and economic sustainability of the process required an adequate thickening of sludge/digestate. Abstract: Reduced biodegradability of waste activated sludge (WAS) limits the production of methane and the consequent energy recovery in an anaerobic digestion (AD) process. Pre-treatments are a solution to increase the biodegradability of bacteria cell biomass, but a large part of poorly degradable organic matter is left after digestion. The utilization of intermediate hydrolysis treatments (IHTs) may help in converting even the most recalcitrant parts of organic matter in methane. This study employed a three-phase experimentation to assess the effect of the hydraulic retention time (HRT) of the digestion first stage, on the overall performance of a two-stage digestion process, with an in-between treatment, carried out on WAS. The three phases of the experimentation included a first-stage digestion (with HRTs = 5, 10 and 15 days), performed in a semi-continuous 10L-reactor, followed by a thermal (90 °C) or a hybrid (thermal 90 °C + chemical, 4% NaOH) IHT, completed by a second-stage digestion carried out in a batch mode. Both the digestion processes were performed in mesophilic conditions (38 °C). The obtained results revealed that, in the presence of a thermal IHT and by fixing the duration of the second stage to 20 days, the overall specific methane production (SMP) tended to a constant value, in the order of 0.205 Nm 3 /kg VS added, irrespective of the duration of the first stage. Conversely, when a hybrid treatment was applied, the difference between a short (5 days) and a medium (10–15 days) duration of the digestion first stage became evident, with SMPs in the order of 0.247 and 0.230 Nm 3 /kg VS added, respectively. Energy and economic sustainability of the application of IHTs at a full scale plant required an adequate thickening of sludge/digestate matrices and an efficient heat exchange between donor (sludge after treatment) and acceptor (cold sludge before digestion) agents. It was demonstrated that for separated or joined digestion processes of primary sludge (7.0% TS) and treated digestates, with heat recovery and different combinations of the duration of the first and second stage of AD, TS contents in the order of 4%, 6% and 8–9% were required to make the thermal balance neutral for thermal exchanges efficiencies of 100%, 70% and 50%, respectively.